Succesful treatment of extravasation injury with topical heparinoid in a pediatric patient - Ozcan, Alper; Betul Ergul, Ayse; Akbiyik, Demet; Altuner Torun, Yasemin (Annals of Medical Research, 2021)
None
Keywords: None